Gregorio Peces-Barba and Norberto Bobbio: history of a friendship in 70 letters - Losano, Mario G. (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The scientific and political interests of the legal philosophers Gregorio Peces-Barba (1938-2012) and Norberto Bobbio (1909-2004) are reflected in over 70 letters written between 1978 and 2004, i.e. in the years when in Spain entered into force the new democratic constitution. A recurring theme of this correspondence is the different approach, in both countries, to the coexistence between socialism and democracy as well as with communism and eurocommunism. The result is a lively picture of the Bobbio’s relationship with the Spanish politicians. The present essay includes also some sentences of seminal relevance taken from the letters of each of the two, as well as Peces-Barba’s words commemorating Bobbio’s death in the Spanish press: words testifying not only the political affinity, but also the personal affection of both scholars.